Studies into the effects of the vaccinia virus protein A46R on Interleukin-1/Toll-Like receptor signalling pathways - Stack, Julianne (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2005)
Poxviruses circumvent the host immune response by encoding proteins that can antagonise host defence mechanisms. The vaccinia virus (VV) protein, A46R, was identified based on sequence similarity to the Toll/Interleukin-1/Resistance homology (TIR) domain, the cytosolic signalling domain of the interleukin-1 receptor (IL-IR ) and Toll-like receptors (TLRs). TLRs play a crucial role in host defence against invading micro-organisms by mediating pro-inflammatory signalling cascades, mainly through their cytoplasmic TIR domains. A46R is the only viral protein so far identified to have a TIR domain. Initial studies revealed that A46R could inhibit IL-1, but not tumour necrosis factor (TNF) a-induced NFkB activation (Bowie et al, 2000), suggesting a role for the protein in immune evasion. This study shows that A46R also blocked multiple signals em anating from TLR4, suggesting that it was acting on a molecule close to the receptor complex that was also required for IL-1 signalling. Immunoprecipitation and GST-pulldown experiments revealed that A46R targeted MyD88, a TIR adaptor molecule used by both IL-1 and TLR4, while further studies showed A46R blocked MyD88-dependent pathways in murine macrophages. This is the first example of a viral protein targeting MyD88.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin